Pathogenesis, diagnosis and treatment of immune checkpoint inhibitor related bullous pemphigoid - Yi SUN; Ji YANG (Zhongguo Linchuang Yixue)
As a new type of anti-tumor therapy, immune checkpoint inhibitor (ICI) can effectively improve the survival rate of tumor patients, but also bring a series of adverse reactions. Among these, immune-related cutaneous adverse events are prevalent. There is a relatively low incidence of bullous pemphigoid (BP) induced by ICI. However, this adverse event may not only negatively impact patient quality of life of patient, but also lead to treatment interruptions or discontinuations. This paper reviews the pathogenesis, prevalence, clinical manifestations, management methods of BP induced by ICI and its effect on tumor immunotherapy.